Medicated Meloxicam Pellets Reduce Some Indicators of Pain in Disbudded Dairy Calves - Tiarna Scerri; Sabrina Lomax; Peter Thomson; Benjamin Kimble; Peter White; Merran Govendir; Cameron Clark; Dominique Van der Saag (Animals)
Disbudding is a husbandry practice that causes pain and discomfort to calves. As a prominent welfare concern, it is now standard practice for calves to be given analgesic treatment such as a nonsteroidal anti-inflammatory drug (NSAID) injection. Meloxicam is a commonly used NSAID as it provides pain relief for up to 44 h following disbudding. However, since symptoms can persist for up to two weeks, it was hypothesised that more prolonged analgesic treatment would promote better welfare outcomes than the conventional injection. This study tested a novel treatment whereby disbudded calves were fed grain-based pellets medicated with meloxicam over a 7-day period. Lower levels of horn site inflammation were observed for the pellet treatment across the 7-day feeding period in comparison to the conventional injection. The pellet treatment calves also exhibited less pain-specific and more positive social-specific behaviours during and beyond the feeding period. Together, these results suggest that lower levels of inflammation enacted by prolonged meloxicam administration have an active role in reducing pain and maintaining the affectivity of disbudded calves. With the goal of establishing sustained disbudding treatment as a new industry standard, future research will focus on larger-scale results reproducibility and maximising treatment practicality.